Kelas Edukasi Menyusui Sebagai Penunjang Keberhasilan Memberikan ASI Eksklusif - Shelly Puspa Anggraini; Retna Siwi Padmawati; Madarina Julia (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Breastfeeding education classes as a support for exclusive breastfeeding successPurposeThe purpose of this paper was to examine the difference of maternal participation in breastfeeding education class AIMI (Indonesian Breastfeeding Association) and the success of exclusive breastfeeding.MethodA cross-sectional study was conducted involving 186 mothers. We used in-depth interviews of mothers who had attended AIMI Yogyakarta's breastfeeding education class.ResultsAs many as 88.6% of respondents gave exclusive breastfeeding. Of those who attended only one class, 88.9% gave exclusive breastfeeding, while 88.6% in the group who attended the two educational classes gave exclusive breastfeeding. There was no difference between mothers who attended one class or two classes of education on exclusive breastfeeding success.ConclusionThis study contributes to the knowledge that there is no difference between mothers attending one class or two classes of education on exclusive breastfeeding success.